Optimizing pegylated asparaginase use: An institutional guideline for dosing, monitoring, and management. (January 2020) - Bade, Najeebah A; Lu, Crystal; Patzke, Ciera L; Baer, Maria R; Duong, Vu H; Law, Jennie Y; Lee, Seung T; Sausville, Edward A; Zimrin, Ann B; Duffy, Alison P; Lawson, Justin; Emadi, Ashkan
The incorporation of L-asparaginase and pegylated asparaginase into pediatric-inspired regimens has conferred a survival advantage in treatment of adults with acute lymphoblastic leukemia. Use of asparaginase products requires careful prevention, monitoring, and management of adverse effects including hypersensitivity, hepatotoxicity, pancreatitis, coagulopathy, and thrombosis. Currently, there is limited published literature to offer guidance on management of these toxicities. At the University of Maryland Marlene and Stewart Greenebaum Comprehensive Cancer Center, a standard of practice guideline was created to prevent and manage asparaginase-related adverse events. By sharing our long-term experience with asparaginase products and clinical management of asparaginase-induced toxicities, this article aims to improve patient safety and optimize treatment outcomes.